Impact of scCO2-rock interaction on fracturing performance in Shale reservoirs - Memon, Shoaib (Curtin University, 2024)
The study investigated how injecting CO2 during hydraulic fracturing impacts the shale rock. It conducted multiple fracturing tests using CO2 on different shale samples, characterising them before and after fracturing to understand the changes. Results show CO2 affects rock properties, specially in clay-rich shales. The study also confirms the importance of injected CO2 pressurisation rate, affecting both the breakdown mechanism and the characteristics of the CO2-induced fractures.